Hydromorphone Prescription for Pain in Children—What Place in Clinical Practice? - Rodieux, Frédérique; Ivanyuk, Anton; Besson, Marie; Desmeules, Jules; Samer, Caroline F. (Frontiers in Pediatrics, 2022)
While morphine is the gold standard treatment for severe nociceptive pain in children, hydromorphone is increasingly prescribed in this population. This review aims to assess available knowledge about hydromorphone and explore the evidence for its safe and effective prescription in children. Hydromorphone is an opioid analgesic similar to morphine structurally and in its pharmacokinetic and pharmacodynamic properties but 5 to 7 times more potent. Pediatric pharmacokinetic and pharmacodynamic data on hydromorphone are sorely lacking; they are non-existent in children younger than 6 months of age and for oral administration. The current data do not support any advantage of hydromorphone over morphine, both in terms of efficacy and safety in children. Morphine should remain the treatment of choice for moderate and severe nociceptive pain in children and hydromorphone should be reserved as alternative treatment. Because of the important difference in potency, all strategies should be taken to avoid inadvertent administration of hydromorphone when morphine is intended.